EXAMINATION OF THE RELATIONSHIP BETWEEN SOME COORDINATIVE ABILITIES OF CHILDREN WRESTLERS - PEKER, Alper Tunga; TAŞKIN, Mine; VURAL, Mustafa; ÇORUH, Yaşar; ZENGİN, Serkan (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2019)
Aim of this study was to examine the relationship between some coordinative abilities of wrestler children. 26 wrestler children whose mean age was 13.52±0.510 years, mean body height was 1.53±0.075 meters and mean body weight was 49.20±12.987 kilograms, were included in the research by taking consent of their families. All risks and benefits related to the research were explained to the parents of the athletes and they were asked to sign the university approved voluntary consent form. Numbered medicine ball run test, backward medicine ball throw test, and sprint at the given rhythm test were used to determine orientation, differentiation and rhythm performances of research participants related to coordinative abilities. SPSS 22 program was used to analyze data related to measurements made within the scope of the research. Descriptive statistics were used to determine mean and standard deviations related to ages, body heights, body weights, rhythm periods, orientation periods and differentiation scores of wrestler children participating in the research. Pearson correlation analysis was used to examine relationships between rhythm periods, orientation periods and differentiation scores. When results related to the research were examined, it was determined that there was not any significant difference between wrestlers’ rhythm periods and orientation periods, rhythm periods and differentiation scores, orientation periods and differentiation scores (P>0.05).